On the lacunary (A, ϕ) -statistical convergence of double sequences - Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We extend some results known from the literature for ordinary (single) sequences to multiple sequences of real numbers. Further, we introduce a concept of double lacunary strong (A, ϕ)-convergence with respect to a modulus function. In addition, we also study some relationships between double lacunary strong (A, ϕ)-convergence with respect to a modulus and double lacunary statistical convergence.